FOOD HABITS AND ONTOGENETIC CHANGES IN THE DIET OF WHITEFISH LARVAE IN LAKE ANNECY - ANNEVILLE O. (Knowledge and Management of Aquatic Ecosystems, 2007)
The ontogenetic changes in the diet of whitefish (Coregonus lavaretus) larvae were investigated during three consecutive years in a deep peri-alpine lake. Identification of the feeding habits of larvae in relation to their larval stage was performed using a PCA% in order to take into account the individual variability in larval diet. Although whitefish larvae are planktivorous, the present study points out ontogenetic changes in diet. While young larval stages are opportunistic feeders on small copepods, older stages feed preferentially on Daphnia sp.. Strong inter-annual variability has been observed in the dietary overlap between the successive larval stages. We show that the density and availability of the potential prey will affect the dynamics of the ontogenetic changes in the diet. Furthermore, it could probably alter the intra-specific competition between larval stages.